The effect of rotor design on rotor slot harmonics in induction machines - Guldemir, H; Bradley, KL (Taylor & Francis Inc, 2001)
This paper looks at the effect of different rotor designs on rotor slot harmonics (RSH) in induction-motor, line-current, spectra. The magnitude and the frequency of the rotor slotting harmonics for a number of different rotor designs have been obtained experimentally to identify which of the motor design parameters have significant effect on these harmonics. A computational model has also been developed using the mmf-permeance technique incorporating the effect of saturation, skew, slot-openings, static eccentricity, and the number of rotor slots on these harmonies. The model has been validated using the experimental data. This enables the effect of rotor design changes to be investigated over a wider range of variation than is possible experimentally. The model also facilitates an understanding of the reasons why design changes have the effect they have.
Keywords: Orientation Control; Motor Drives